2012
DOI: 10.1159/000341141
|View full text |Cite
|
Sign up to set email alerts
|

Single-Port Access Total Laparoscopic Hysterectomy for Large Uterus

Abstract: Background/Aims: To evaluate the feasibility and safety of single-port access total laparoscopic hysterectomy (SPA-TLH) for large uterus (>500 g). Methods: A prospective data collection was performed in 21 consecutive patients in March 2010 and August 2011. Surgical outcome including operative time (OT) and estimated blood loss (EBL) were analyzed. Results: SPA-TLH procedures were successfully performed in 16 cases (76.2%). Of the 5 failed cases, 4 were converted to multiport TLH because of distorted uterine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…SPA‐TLH has previously been shown safe and feasible [4]. The present study provides further evidence of the safety and feasibility of this procedure, which can be facilitated by unidirectional barbed sutures.…”
supporting
confidence: 62%
“…SPA‐TLH has previously been shown safe and feasible [4]. The present study provides further evidence of the safety and feasibility of this procedure, which can be facilitated by unidirectional barbed sutures.…”
supporting
confidence: 62%
“…The median operative time, uterine weight, and EBL were 110 (65-165) min, 600 (502-980) g, and 200 (100-800) ml, respectively. These studies demonstrated that operative time and EBL increased with the growth of uterine weight (P ¼ 0.003 and P ¼ 0033), and no intra-operative and early postoperative complications were registered [21].…”
Section: Key Pointsmentioning
confidence: 82%
“…For this reason, in many published studies, uterine size is included in the inclusion criteria. Nonetheless, Song et al [21] showed the feasibility of single-port hysterectomy also in uteri with a weight more than 500 g with a successful rate of 76.2%. The median operative time, uterine weight, and EBL were 110 (65-165) min, 600 (502-980) g, and 200 (100-800) ml, respectively.…”
Section: Key Pointsmentioning
confidence: 99%
“…With the minimally invasive approach, the single incision laparoscopic technique has both advantages over laparotomy, such as faster return to normal activities, shorter duration of hospital stay, and reduced pain, as well as advantages over multi-incision laparoscopic surgery, such as improved cosmetics and reduced risks related to trocar insertion, for example, vessel injury, hematoma and infection [15,16,17]. Because of these advantages, single-site hysterectomy seems feasible but has considerable limitations, especially technical limitations, as previously mentioned.…”
Section: Discussionmentioning
confidence: 99%